Professional burnout of doctors in Poland and in the world. Research review - Zwolak, Agnieszka; Kruk, Edyta; Brodowicz-Król, Magdalena (Journal of Education, Health and Sport, 2022)
The work of a doctor is one of the most demanding. It requires not only a great deal of knowledge, but also a lot of commitment, responsibility and often devoting one's private life. It is called a prestigious job for a reason. Unfortunately, it is also very absorbing both mentally and physically. Increasing stress leads to emotional exhaustion, and its consequence may be burnout.